Physical rehabilitation in the context of a landslide that occurred in Brazil - M. L. Carvalho; C. M. Freitas; E. S. Miranda (BMC, 2019)
Abstract Backgrounds The efforts to develop research and training on physical rehabilitation in regards to disasters is considered recent worldwide. In the late evening of the 11th up until the 12th of January of 2011, the most massive natural disaster occurred in Brazil with extremely heavy downpour, abrupt flood, as well as landslides on multiple areas of the Mountain Region of Rio de Janeiro. The objective of this research was to investigate the challenges in terms of physical rehabilitation provided by this event Methods The cross-sectional mixed method's study, which was conducted in the city of Nova Friburgo, used two different data sources: hospital records on traumatic injuries pre and post disaster, and interviews with key informants - victims who suffered injuries related to the disaster, professionals from rehabilitation services in the municipality, and also the city's health service management. Pearson's chi-squared test was performed to evaluate statistical significance between the week of a given incident and the type of injury. Interviews were transcribed and analysed through content analysis. Results A total of 2326 hospital records and 27 interviews were analysed. The proportion of traumatic injury in the municipal emergency service increased from 16% in the prior week, to 40% in the week post-disaster (p <  0.0001). Different injuries were identified: multiple fractures, crushing, amputation, perforation of soft tissues, inhalation of dust and establishment of chronic conditions through stress. Despite this scenario, out of the 16 health professionals interviewed, twelve did not observe an increase in the demand for outpatient rehabilitation services after the disaster. Interviews with the victims revealed that the pathways for care ran into different barriers. From 11 victims interviewed, only one received complete physiotherapy care through the public health services in the city, while all others hired additional assistance, received volunteer services, had assistance in other cities or remained without rehabilitation. Conclusions The needs for rehabilitation increased after the disaster; however, the demand was repressed due to different barriers such as competing needs and possible lack of medical referral. Recommendations were made, including the action of performing a search of victims with rehabilitation needs.